Effects of a 12-week HIIT + group mediated cognitive behavioural intervention on quality of life among inactive adults with coeliac disease: findings from the pilot MOVE-C study. Issue 4 (3rd April 2022) - Dowd, A. Justine; Kronlund, Liam; Warbeck, Cassandra; Parmar, Candice; Daun, Julia T.; Wytsma-Fisher, Kathryn; Reimer, Raylene A.; Millet, Guillaume; Fung, Tak; Culos-Reed, S. Nicole
Abstract: Objective: The purpose of the pilot MOVE-C study was to examine the effects of a 12-week high-intensity interval training (HIIT) plus lifestyle education program on quality of life (QoL), behavioural and psychosocial outcomes among inactive adults with coeliac disease. Design: This study used a 3 (time: baseline, immediately post and three months post) × 2 (group: experimental versus waitlist control) mixed design. After completing baseline testing, 41 participants were randomised to one of two groups: HIIT + or waitlist control (WLC). The HIIT + intervention involved twice-weekly HIIT, during which participants progressed to 14 × 30 s intervals (90% heart rate max; HRmax), with 2-minute recovery (50% HRmax). The HIIT + intervention also included six bi-weekly education sessions. Results: Participants in HIIT + reported significant improvements in QoL and exercise behaviour immediately post-intervention, and this was sustained three months post-intervention, whereas no changes in QoL nor exercise behaviour were reported in WLC. Improvements were also reported among HIIT + immediately after the intervention for gastrointestinal symptoms and self-compassion. All participants reported significant improvements in adherence to a GFD immediately post-intervention. Conclusion: Findings from this pilot study provide preliminary evidence that a tailored exercise and lifestyle intervention can lead to improved QoL, exercise behaviour, gastrointestinal symptoms and self-compassion among inactive adults with coeliac disease.